The Routledge Handbook of language and identity - Preece, Sian (Routledge handbooks in applied linguistics, 2016)
Forty-one chapters are organised into five sections covering: theoretical perspectives informing language and identity studies; key issues for researchers doing language and identity studies; categories and dimensions of identity; identity in language learning contexts and among language learners; future directions for language and identity studies in applied linguistics.